Current allocations and target apportionment for HIV testing and treatment services for marginalized populations: characterizing PEPFAR investment and strategy. (30th June 2021) - Jones, Austin; Honermann, Brian; Lankiewicz, Elise; Sherwood, Jennifer; Millett, Greg
Abstract: Introduction: The United States President's Emergency Plan for AIDS Relief (PEPFAR) is a large bilateral funder of the global HIV response whose policy decisions on key populations (KPs) programming determine the shape of the key populations' response in many countries. Understanding the size and relative share of PEPFAR funds going to KPs and the connection between PEPFAR's targets and resulting programming is crucial for successfully serving key populations. Methods: Publicly available PEPFAR budgets for key populations' services were assessed by country and geographical region for all 52 countries with budget data in fiscal year (FY) 2020. For the 23 countries which completed a full planning process in FY 2018 and 2019, PEPFAR targets for HIV testing and treatment initiation for key populations were assessed. Expenditures for KP programming were calculated to determine whether shifts in targets translated into programming. Implementing partners were characterized by the level of specialization using the share of assigned targets made up by KPs. The average target per year and implementing partner was calculated for each KP group and indicator. Results: PEPFAR country KP budgets ranged from US35, 000 to 15.2 million, and the proportion of funding to key populations varied by region, with Eastern and Southern African countries having the lowest proportion. Between FY 2018 and 2019, the KP targets for HIV testing and treatment among KPs increased, whereas expenditures on key populations decreased from US115.4 to 111.0 million. Of the 11 countries with an increase in HIV testing targets, seven had a decrease in KP expenditures. Of the nine countries with an increase in treatment initiation targets, five had a decrease in KP expenditures. The proportion of targets assigned to partners which do not specialize in key populations increased from FY 2018 to 2019. Conclusions: Current key population policies have not resulted in a tight connection between targets and expenditures. This includes assigning a large proportion of key populations programming to partners who do not specialize in key populations, which may weaken the performance management role of the targets. These results signal that a new approach to key populations programming is needed.